1996
DOI: 10.1021/jp953304u
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Properties of Nickel(II) Octaethylporphyrin in Solution. 2. A Low-Temperature Optical Absorption Spectroscopy Study

Abstract: We have measured the absorption spectrum of Ni(II) octaethylporphyrin in CH2Cl2 and in a 50% v/v isopentane/ethyl ether mixture as a function of temperature between 150 and 300 K and 40 and 300 K, respectively. The Soret band can be decomposed into two subbands whose frequencies differ by 220 cm-1. By analogy with resonance Raman results (Jentzen et al. J. Phys. Chem. 1996, 100, 14184−14191 (preceding paper)), we attribute the low-frequency subband to a conformer with a nonplanar macrocycle structure, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 33 publications
4
30
1
Order By: Relevance
“…* 7 transitions with in-plane vibrational modes of organic macrocycles (Schomacker and Champion, 1986). 3. In agreement with expectations of the literature (Schomacker and Champion, 1989;Cupane et al, 1996), no relevant temperature dependence of coupling constants is observed; in fact, eventual variations of S values are within +5%. For this reason, S values were taken to be constant in the fittings of the spectra at various temperatures.…”
Section: Spectral Analysissupporting
confidence: 92%
“…* 7 transitions with in-plane vibrational modes of organic macrocycles (Schomacker and Champion, 1986). 3. In agreement with expectations of the literature (Schomacker and Champion, 1989;Cupane et al, 1996), no relevant temperature dependence of coupling constants is observed; in fact, eventual variations of S values are within +5%. For this reason, S values were taken to be constant in the fittings of the spectra at various temperatures.…”
Section: Spectral Analysissupporting
confidence: 92%
“…1) listed in Table 7 were now used to estimate υQ Table 9. Apparently, 15 B 2u is substantially weaker coupled to the B-state transition than the investigated A 2u and B 1u modes. Its strong Raman intensity is due solely to the comparatively strong saddling distortion of the macrocycle.…”
Section: Evaluation Of Heme Deformationsmentioning
confidence: 68%
“…to compare them to the coupling constants S hj obtained from the fit of the lineshape of the Soret band (Cupane et al, 1996a). The frequency of the mode is denoted by hj .…”
Section: Resonance Raman Measurementsmentioning
confidence: 99%